Interleukin-12 Inhibits Tumor Growth in a Novel Angiogenesis Canine Hemangiosarcoma Xenograft Model - Akhtar, Nasim (Neoplasia Press Inc., 2004)
We established a canine hemangiosarcoma cell line derived from malignant endothelial cells comprising a spontaneous tumor in a dog to provide a renewable source of endothelial cells for studies of angiogenesis in malignancy. Pieces of the hemangiosarcoma biopsy were engrafted subcutaneously in a bg/nu/XID mouse allowing the tumor cells to expand in vivo. A cell line, SB-HSA, was derived from the xenograft. SB-HSA cells expressed vascular endothelial growth factor (VEGF) receptors 1 and 2, CD31, CD146, and α(v)β(3) integrin, and produced several growth factors and cytokines, including VEGF, basic fibroblast growth factor, and interleukin (IL)-8 that are stimulatory to endothelial cell growth. These results indicated that the cells recapitulated features of mitotically activated endothelia. In vivo, SB-HSA cells stimulated robust angiogenic responses in mice and formed tumor masses composed of aberrant vascular channels in immunocompromised mice providing novel opportunities for investigating the effectiveness of antiangiogenic agents. Using this model, we determined that IL-12, a cytokine with both immunostimulatory and antiangiogenic effects, suppressed angiogenesis induced by, and tumor growth of, SB-HSA cells. The endothelial cell model we have described offers unique opportunities to pursue further investigations with IL-12, as well as other antiangiogenic approaches in cancer therapy.